Time-Shared Computers in Business Education at Dartmouth. - Bower, Richard S.; Nugent, Christopher E.; Stone, Donald E. (The Accounting Review, 1968)
Abstract To respond to the challenge to produce business school graduates who are intelligent users of computer power requires a significant commitment. Yet it is a challenge that must be met. At the Amos Tuck School access to time-shared computer power has given us the hardware characteristics necessary to provide computer accessibility to all our students on a demand basis. Through a formal computer course at the start of the two-year curriculum the student gains the familiarity and technical skill necessary to permit him to make intelligent use of the computer in his other courses at Tuck. As this formal instruction is reinforced in his other courses the student builds his confidence and skill in applying computer power to a wide variety of problems and situations. Many of these applications are formally structured into the curriculum; others are developed by the student simply because he saw a situation where the computer would help him perform more efficiently. Computer education of this sort produces at least two challenges to the faculty. Because readily available computational power can allow the student to learn more and understand better, the faculty is challenged to continue to look for areas within their courses where computer usage might reap these benefits. The second challenge is one of software design to make the computer more useful to the student in studying and solving business problems. The LAFFF language is the first major attempt at business-oriented software design, but certainly not the last. Responding to these challenges is beneficial to the teacher both in his teaching and research activities. More importantly, we feel it is beneficial to our students. These efforts, coupled with the impressive capabilities of time-shared computer facilities, produce an educational environment of unusual potential. Our efforts related here represent only a small start towards realization of the full potential.